Pembuatan Sistem Informasi Management User, Management Praktikum dan Registrasi Praktikum Berbasis Website di Jurusan Teknik Informatika Institut Teknologi Adhi Tama Surabaya Menggunakan Metode Waterfall - Khisby Al Ghofari; Muchamad Kurniawan; March Angga V. W; Aldi Wachid Arifin (Institut Teknologi Adhi Tama Surabaya, 2021)
Practicum is a lecture activity carried out in the laboratory. Practicum aims to help students understand lecture material more quickly by practising it in the laboratory. There are three laboratories for Informatics Engineering at the Adhi Tama Institute of Technology Surabaya, namely the Software Engineering Laboratory, the Programming Language Laboratory and the Computer Network Laboratory. The Laboratory Registration System still uses conventional methods by bringing requirements to the laboratory for data collection. As well as an assessment system that still uses the Microsoft Excel application media so it is less fast and less efficient. This study aims to create a practicum information system with the Waterfall method at the Informatics Engineering Laboratory of the Adhi Tama Institute of Technology Surabaya. The test results show that the Waterfall method can be used to create a practicum information system so that it helps make the practicum easier, more efficient, structured and safer.